1991
DOI: 10.1182/blood.v77.5.1020.bloodjournal7751020
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of heparin for arterial and venous thrombolysis with recombinant tissue-type plasminogen activator

Abstract: The effect of concomitant intravenous (IV) heparin (200 U/kg bolus, followed by 100 U/kg/h) on the efficacy of arterial and venous thrombolysis with IV recombinant tissue-type plasminogen activator (rt- PA; 0.5 mg/kg over 1 hour) was investigated in a combined femoral arterial and venous thrombosis model in the dog. The arterial model consisted of a high-grade stenosis, endothelial damage, and a thrombotic occlusion, and the venous model consisted of a 125I-fibrin- labeled blood clot. After a dose-finding pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Because of the small size of this study, little significance can be attached to the finding of rethrombosis in one of the t‐PA animals. However, this event is consistent with previous studies in t‐PA‐treated dogs [23], with clinical studies in which a 25–30% early coronary reocclusion incidence was reported with t‐PA [24], and with reports that the efficacy of percutaneous coronary intervention over t‐PA was related to a higher reocclusion rate with t‐PA [25]. By contrast, coronary reocclusion rates of only 0–5% were reported with proUK [2,26,27], and markers of thrombin generation in plasma were not induced by proUK [26], in contrast to t‐PA [28].…”
Section: Discussionsupporting
confidence: 94%
“…Because of the small size of this study, little significance can be attached to the finding of rethrombosis in one of the t‐PA animals. However, this event is consistent with previous studies in t‐PA‐treated dogs [23], with clinical studies in which a 25–30% early coronary reocclusion incidence was reported with t‐PA [24], and with reports that the efficacy of percutaneous coronary intervention over t‐PA was related to a higher reocclusion rate with t‐PA [25]. By contrast, coronary reocclusion rates of only 0–5% were reported with proUK [2,26,27], and markers of thrombin generation in plasma were not induced by proUK [26], in contrast to t‐PA [28].…”
Section: Discussionsupporting
confidence: 94%
“…The pharmacologic actions of heparin include 1) facilitation of the effect of antithrombin by inhibiting thrombin activity 11 ; 2) attenuation of platelet aggregation"; 3) inhibition of conversion of fibrinogen to fibrin 12 ; 4)facilitation of release of plasminogen activator 13 ; 5) potentiation of thrombolysis by combination with thrombolytic agents 1415 ; and 6) increase in the blood level of tissue factor pathway inhibitor (TFP1), an exogenous inhibitor of coagulation derived from vascular endothelial cells. 16 Although heparin is not considered to have a direct thrombolytic action, Susawa 14 and Rapold et al 15 reported the usefulness of heparin in thrombolysis. In addition, Yamamoto et al 17 reported that the intravenous injection of heparin 5,000 U could support recanalization of the coronary arteries in an early phase, within 2 hr after the onset of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of our study was to evaluate the thrombolytic and haemorrhagic effects of a bolus of rt-PA and K2tu-PA, a chimeric tissue-type and urokinase-type plasminogen activator with prolonged half life. We found that the two agents are equally effective in lysing pre-formed fibrin but (32,33). Such doses would not be used in humans because of the high risk of bleeding.…”
Section: Discussionmentioning
confidence: 89%